Crime and Punishment in the Cape Breton Songs Contest - Brodie, Ian (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2019)
Dishpan Parade, a morning women’s entertainment program, was a production of Sydney, Nova Scotia’s CJCB Radio from 1948 to 1952. Early in its run the hosts created a local song contest, rewarding lyrics on a Cape Breton theme set to known melodies. Many entrants took the opportunity to satirize current events, protected by the implied triviality of light verse. This article places two such songs—“Bootleg Coal,” set to “The Blue-Tail Fly,” and “Go Away (The County Jail)” to “Polly Waddle Doodle” — within the specific history that occasioned them and suggests the expressive and subtle subversiveness of mid-century Cape Breton women.